GENDER DEMOGRAPHIC DISPARITIES IN BACAU COUNTY - Stangaciu, Oana Ancuta; Harja, Eugenia (Studies and Scientific Researches. Economics Edition, 2014)
Gender demographic disparities existing in Bacau County were determined by means of some demographic indicators such as: population, natural growth, live births, marriages, divorces, indicators which have been broken down by gender. The assessment of the disparities between men and women from the point of view of the demographic phenomena emphasize the fact that on the level of Bacau County there is a surplus of female population, as during the whole period subjected to the analysis, the positive and respectively the negative natural growth for the male population were lower and higher respectively than the one registered in the case of the female population. The birth rate, marriage rate and divorce rate phenomena also changed significantly after 1990 ; thus, the average age of marriage increased, and the gender difference also had a certain growth, which caused a shift in the fertility intensity from the age group 20-24 to the very next one - the 25-29 age group.